Composites Made of Carbon Nanotubes and Silver Nanoparticles for Conductive Aerosol-Jet Deposition Ink: The Double-Edged Sword of Functionalization - Schulman, Omri; Samira, Raz; Lachman, Noa (Frontiers in Materials, 2022)
Optimizing conductive ink for Direct-Write Additive Manufacturing, this work explores the effect of carboxylic functionalization of multi-walled carbon nanotubes (CNTs) on their affinity to silver nanoparticles (NPs) deposited on them. We show a correlation between functionalization and the size of the resulted NPs: the diameter of the silver NPs deposited on pristine CNTs (~5 nm diameter) is third of that of NPs deposited on functionalized CNTs (~15 nm). Electrical characterization of the silver-decorated CNT-based ink shows a more significant improvement in conductivity of the functionalized CNTs-decorated with silver compared to the pristine one (maximal ~40% and ~20% increase in conductivity over their undecorated counterpart, respectively). However, CNT functionalization severely damages the conductivity of the CNTs themselves, resulting in a much lower conductivity. This “double-edged sword” effect of functionalization results in the highest absolute specific conductivity (3.79 x 103 S/m) achieved by decorating pristine CNTs with 25 wt.% of silver. Nevertheless, the observed enhanced conductivity and the ability to control the composite’s morphology by functionalization allow fine-tuning of morphology-based properties, such as surface enhanced Raman scattering and optimization of the ink for sensing applications.